Tyrosinase/caffeic acid cross-linking alleviated shrimp (Metapenaeus ensis) tropomyosin-induced allergic responses by modulating the Th1/Th2 immunobalance. (15th March 2021) - Ahmed, Ishfaq; Lin, Hong; Li, Zhenxing; Xu, Lili; Qazi, Ihsan Mabood; Luo, Chen; Gao, Xiang; Khan, Mati Ullah; Iqbal, Amjad; Guo, Yuman; Pavase, Tushar Ramesh; Sun, Lirui
Highlights: Tyr/CA crosslinking of TM effectively inhibited the cellular degranulation. TM-Tyr/CA showed enhanced digestion stability and reduced immunoreactivity. Moreover, this method effectively reduced the allergic responses in mice model. TM-Tyr/CA showed promise in developing hypoallergenic shellfish products. Abstract: In this study, the effect of enzymatic cross-linking of shrimp tropomyosin (TM) with tyrosinase and caffeic acid (TM-Tyr/CA) on the allergic response were assessed using in vitro and in vivo models. The RBL-2H3 and KU812 cell lines were employed to evaluate the changes in the stimulation abilities of TM-Tyr/CA that showed significant inhibition of mediators and cytokines. The digestibility of cross-linked TM was improved and the recognitions of IgG/IgE were markedly reduced, as revealed by western blotting. TM-Tyr/CA decreased anaphylactic symptoms, and hindered the levels of IgG1, IgE, histamine, tryptase and mouse mast-cell protease-1 (mMCP-1) in mice sera. Cross-linked TM downregulated the production of interleukin (IL)-4, IL-5, and IL-13 by 51.36, 12.24 and 20.55%, respectively, whereas, IL-10 and IFN-γ were upregulated by 20.71 and 19.0%. TM-Tyr/CA showed reduced allergenicity and may have preventive effect in relieving TM induced allergic response via immunosuppression and positive modulation of T -helper (Th)1/Th2 immunobalance.